MGF-North Sea II: CTD data from the Amrumbank and Borkum Reef Ground (German Exclusive Economic Zone) - Moritz Sonnewald (PANGAEA, 2025)
These CTD profiles were taken by RV Senckenberg of the Senckenberg Research Institute in the framework of the MGF-North Sea project (phase 2) at the German Exclusive Economic Zone (EEZ) of the North Sea. There, the NATURA2000 sites Amrumbank (AMB), Sylt Outer Reef (SAR) and Borkum Reef Ground (BRG) were visited in 2023 and 2024. At each station, a CTD probe (Sea & Sun Technologies, CRD48) was lowered to the seabed, recording temperature and salinity each second. The dataset was trimmed and thus contains the records from each station during the individual heaving phases. Altogether, the dataset contains data from five cruises. Namely they are (with month / year in brackets) [and number of stations in square brackets]: AMB23-2 (August 2023) [4], AMB23-3 (October 2023) [4], BRG24-1 (May 2024) [8], BRG24-2 (July 2024) [4] and BRG24-3 (October 2024) [4].